PENGARUH MEDIA LAGU TERHADAP MINAT BELAJAR PESERTA DIDIK PADA PELAJARAN IPA DI SDN KARANGBALE 01 - Widyastuti, Suciati Rahayu (LPPM UNU CIREBON, 2024)
Abstract: The aim of this research was to find out the results of the interest analysis of class V students at SDN Karangbale 01 towards science lessons before the implementation of song media, to find out the results of the analysis of interest of class V students at SDN Karangbale 01 towards science lessons after the application of song media, to find out the influence of song media. on students' learning interest in science lessons. The research method uses experimental methods with quasi-experimental types and quantitative approaches. The design in this research is One-Group Pretest-Posttest Design. The population in this study was all students at SDN Karangbale 01, while the sample in this study used a saturated sampling technique, so the sample used in this study was all students in class V, totaling 15 students. The results of this research are the results of the analysis of student interest before the application of song media, categorized as medium at 80% with a frequency of 12, and the high category at 20% with a frequency of 3, while the results of the analysis of student interest before the application of song media are categorized as high with a medium category of 47% with a total frequency of 7, and the high category is 53% with a total frequency, and there is an influence of song media on students' interest in learning. This was obtained from the results of the T Test using Paired samples t Test by comparing the Sig. (2-talled) < 0.05 (0.000 < 0.05) and compare value > (4.608 > 2.14). This shows that H0 is rejected and Ha is accepted, so the hypothesis states